2010
DOI: 10.1177/112067211002000603
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Neovascularization following Central Retinal Artery Occlusion: Prevalence and Timing of Onset

Abstract: The prevalence of neovascularization following acute CRAO in our population was 18.2% at an average of 8.5 weeks post CRAO. There was a temporal relationship between the 2 events and no other causes of neovascularization demonstrable in our cohort of patients. There is no consensus on the follow-up regimen post CRAO to detect ocular neovascularization complications. Our study suggests that neovascularization can occur early and regular follow-up especially in the first 4 months is important post CRAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 15 publications
5
54
0
4
Order By: Relevance
“…The reported prevalence on neovascularization after CRAO varies from 2.5 to 31.6%. 64 Hayreh et al 20 showed no cause-effect relationship between CRAO and ocular neovascularization in their cohort of 232 patients with CRAO. 20 On the other hand, Rudkin et al 64 showed a temporal relationship between the CRAO and neovascularization events, and the patients who developed neovascularization did not have other clinical features, such as diabetes or an association with a haemodynamically significant stenosis of the carotid artery to account for the neovascularization other than CRAO.…”
Section: (B) Preventing Ocular Neovascularization Complication In Thementioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence on neovascularization after CRAO varies from 2.5 to 31.6%. 64 Hayreh et al 20 showed no cause-effect relationship between CRAO and ocular neovascularization in their cohort of 232 patients with CRAO. 20 On the other hand, Rudkin et al 64 showed a temporal relationship between the CRAO and neovascularization events, and the patients who developed neovascularization did not have other clinical features, such as diabetes or an association with a haemodynamically significant stenosis of the carotid artery to account for the neovascularization other than CRAO.…”
Section: (B) Preventing Ocular Neovascularization Complication In Thementioning
confidence: 99%
“…Neovascularization after CRAO tend to occur around 8 weeks (range 2-16 weeks). 64 Therefore, prudent clinical practice would be to review all patients with acute CRAO at regular intervals as early as 2 weeks, and then monthly up to 4 months after CRAO. 64 (C) Long term: preventing other vascular ischaemic events to the eye or other end organ…”
Section: (B) Preventing Ocular Neovascularization Complication In Thementioning
confidence: 99%
“…As well as considering CRAO alone, it considers the concept of double embolism as reported by Wolter 6 as well as CRAO in a setting of chronic ocular ischaemia due to carotid occlusive disease. 7,8 We do, however, strongly agree with Varma et al that such patients should be reviewed at regular intervals for at least 3 months following the diagnosis of CRAO.…”
mentioning
confidence: 62%
“…Neovascularisation is a process of unregulated and misguided growth of new vessels in the eye. 8 Many variables affect neovascularisation, including the extent of ischaemia. Thus, the time to ocular neovascularisation onset ranges from 2 weeks to 4 months post CRAO.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…8 Many variables affect neovascularisation, including the extent of ischaemia. Thus, the time to ocular neovascularisation onset ranges from 2 weeks to 4 months post CRAO.…”
mentioning
confidence: 99%